Advanced imaging techniques in crystal arthritis - Victor Laurent; Georgios Filippou; Silvia Sirotti; Tristan Pascart (Therapeutic Advances in Musculoskeletal Disease)
Gout and calcium pyrophosphate deposition (CPPD) disease are the most common causes of crystal arthritis. Identifying the pathogenic crystal deposition is the cornerstone of the diagnosis, but also prognosis and monitoring of the diseases. Conventional radiography has been for decades the only imaging technique used, with its very restricted sensitivity in both diseases. Advanced techniques, namely ultrasound and dual-energy computed tomography (DECT), are being increasingly used in the diagnosis and management of gout and CPPD diseases, and their role is now well recognized in classification criteria and in recommendations for the diagnosis and management. In gout, ultrasound elementary lesions of monosodium urate deposition are well defined and have been shown to be sensitive to change and can be monitored, while direct quantification of these deposits can be performed with DECT. In CPPD disease, the definition of elementary lesions and their scoring has been well established for ultrasound, while the proof of concept that DECT can help discriminate calcium pyrophosphate crystal deposits among other calcium-containing structures has been shown. The aim of this narrative review is to provide an overview of the use of advanced imaging techniques in crystal-induced arthropathies.